Keputusan Pembelian Melalui Situs Belanja Online terhadap Perilaku Konsumtif Masyarakat dalam Perspektif Ekonomi Islam - Muhammad Ridwan; Isnaini Harahap; Pangeran Harahap (IAIN Langsa, 2018)
This study aims to determine the relationship between purchasing decisions, products, prices, services and risks to consumer consumption behavior in Islamic economic perspective The study will observe Lazada Application Users in Medan. The method used is a quantitative approach using multiple linear regression analysis, with statistical tests. The study found that partially there is a relationship of purchase decision to consumptive behavior by 2.013 or 20.13%. Product to consumptive behavior by 2,137 or 21,37%. Price to consumptive behavior by -2.637 or -26.37%. Service to consumptive behavior by 2,893 or 28,93%. Risk to consumptive behavior by 2.043 or 20.43%. Partially there is a relationship between purchasing decisions, products, prices, services and risks to consumer behavior.